2020
DOI: 10.1155/2020/7415909
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Biomarker hsa-miR-195-5p for Detecting the Risk of Lung Cancer

Abstract: Background. Lung cancer is one of the leading diagnosed cancers worldwide, and microRNAs could be used as biomarkers to diagnose lung cancer. hsa-miR-195 has been demonstrated to affect the prognosis of NSCLC (non-small-cell lung cancer) in a previous study. However, the diagnostic value of hsa-miR-195-5p in lung cancer has not been investigated. Methods. To evaluate the ability of hsa-miR-195-5p to diagnose lung cancer, we compared the expression of hsa-miR-195-5p in lung cancer patients, COPD patients, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In ovarian cancer, overexpression of miR-195-5p can reduce cisplatin resistance and angiogenesis via PSAT1-depedent GSK3β/β-catenin signaling pathway [40]. To date, only four published papers have demonstrated the suppressive role of miR-195-5p in NSCLC cell proliferation and functioned as a predictor of poor prognosis [28][29][30][31]. In line with the published result, our further survival analysis proved that relatively low miR-195-5p expression was associated with unfavorable survival.…”
Section: Discussionsupporting
confidence: 83%
“…However limited studies have demonstrated the role of miR-195-5p in lung cancer. It is reported that miR-195-5p had lower expression in lung cancer and may act as a biomarker that contributed to the diagnosis of lung cancer and the detection of its high-risk population [28,29]. Moreover, miR-195-5p functions as a predictor of poor prognosis by directly targeting CIAPIN1 [30].…”
Section: Ivyspringmentioning
confidence: 99%
“…Moreover, in blood, nine miRNAs including members of the miR-320 family, which target mitogen-activated protein kinase (MAPK) pathways, can be used for lung-cancer prediction in COPD subjects ( 98 ). Finally, the combined expression of hsa-miR-195 and hsa-miR-143, obtained from databases, is able to identify lung cancer compared to disease-free status, but cannot distinguish COPD from lung cancer ( 176 ). From peripheral leucocytes, differential expression of miR-106b-5p, miR-183-5p, miR-125a-5p, and miR-100-5p was found in COPD compared to healthy controls, and miR-106b-5p was directly correlated with disease severity alleviation ( 88 ).…”
Section: Mirnas In Lung Diseasesmentioning
confidence: 99%
“…Gene-TFs and gene-miRNAs basically target main proteins to change the appearance in the progress of particular diseases. Hsa-mir-195-5p, hsa-mir-128-3p, and hsa-mir-129-2-3p target IL6 in these studies [ 74 , 82 ]. Furthermore, hsa-mir-941, hsa-mir-374a-5p, hsa-mir-17-3p, and hsa-mir-129-2-3p are targeted by the FLNC [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%